A Learning Management of Al-Quran and Memorisation through Virtual Learning Environment (VLE) During COVID-19 Pandemic Situation in Malaysia - Abu bakar, Basirah (Online Journal of Research in Islamic Studies, 2022)
On average, it’s not rare for public and private higher institutions to conduct Quranic studies and memorisation during study sessions. The concept of studying Quran and memorisation has been changed according to virtual learning. This happened when movement control order is charged to Malaysian due to Covid-19 pandemic. Hence, the focus of this research is to evaluate implementation and student and teacher’s willingness level in using e-learning during Covid-19. Other than that, this research is also to assess student observations after using e-learning during Covid-19. Thus, these investigations are held by distributing Google form to research sample of 60 people. The sample selection is using the method of simple random sampling. This sample is consisting of Management and Sciences University (MSU), Shah Alam students that involve in the study of Quran and memorisation through online (e-learning). Descriptive statistics using SSPS software used in this study to see the frequency distribution. Result shows that majority of respondents has medium level of knowledge and use of e-learning. The amount of readiness and observation is also at the medium level.